Pengaruh Perkembangan Pasar Modal Syariah dan Inflasi terhadap Pertumbuhan Ekonomi Indonesia pada Tahun 2021-2024 - Aisya Ramadani; Hesi Eka Puteri (ARZUSIN, 2026)
Economic growth is an important indicator in assessing the success of a country’s development. Although the development of the Islamic capital market and inflation has been widely studied, research that specifically analyzes the effect of the market capitalization of Sharia stocks included in the Indonesian Sharia Stock Index (ISSI) and inflation on Indonesia’s economic growth during the 2021–2024 economic recovery period remains relatively limited. This study aims to analyze the effect of ISSI Sharia stock market capitalization and inflation on Indonesia’s economic growth, both partially and simultaneously. This study used a quantitative approach with a causal associative design. The research sample covered all quarterly data for the 2021–2024 period, selected through saturated sampling. Data were collected through documentation from official publications of Statistics Indonesia, Bank Indonesia, the Indonesia Stock Exchange, and the Financial Services Authority, and were then analyzed using multiple linear regression. The results showed that ISSI Sharia stock market capitalization had a positive and significant effect on Indonesia’s economic growth, with a significance value of 0.002. Inflation also had a positive and significant effect on economic growth, with a significance value of 0.000. Simultaneously, the two variables had a significant effect on economic growth, with a significance value of 0.000 and an Adjusted R² value of 0.741. These findings strengthen Keynesian Growth Theory, which emphasizes the importance of investment in driving economic growth, and broaden understanding of the role of the Islamic capital market and macroeconomic stability in national development. The conclusion of this study confirms that ISSI Sharia stock market capitalization and inflation are important factors contributing to Indonesia’s economic growth during the economic recovery period. The implications of this study point to the importance of strengthening the Islamic capital market and controlling inflation to support sustainable economic growth.